2008
DOI: 10.1016/j.biopsycho.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the heritability of task-related brain activation and performance during the N-back working memory task: A twin fMRI study

Abstract: Working memory-related brain activation has been widely studied, and impaired activation patterns have been reported for several psychiatric disorders. We investigated whether variation in N-back working memory brain activation is genetically influenced in 60 pairs of twins, (29 monozygotic (MZ), 31 dizygotic (DZ); mean age 24.4 ± 1.7S.D.). Task-related brain response (BOLD percent signal difference of 2 minus 0-back) was measured in three regions of interest. Although statistical power was low due to the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
105
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 66 publications
14
105
1
2
Order By: Relevance
“…These data extend other recent reports that provide heritability estimates for task-based functional MRI (38)(39)(40), because default-mode connectivity is thought to index more fundamental aspects of brain function than activation evoked by cognitive demands (2,3). Given that default-mode connectivity is readily measureable in nonhuman primates (12), the current results also facilitate the use of resting-state imaging in genetic investigations with animal models.…”
Section: Discussionsupporting
confidence: 84%
“…These data extend other recent reports that provide heritability estimates for task-based functional MRI (38)(39)(40), because default-mode connectivity is thought to index more fundamental aspects of brain function than activation evoked by cognitive demands (2,3). Given that default-mode connectivity is readily measureable in nonhuman primates (12), the current results also facilitate the use of resting-state imaging in genetic investigations with animal models.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast to work on fMRI in hippocampus and amygdala and genetic risk for schizophrenia, previous work from our group and others has shown that excessive BOLD activation in the DLPFC for a fixed level of executive cognition is related to the genetic risk architecture of schizophrenia, constituting an intermediate biologic phenotype (Blokland et al, 2008;Callicott et al, 2003a). This phenomenon is presumed to reflect basic molecular aspects of cortical microcircuit 'tuning' or signal to noise, and has been referred to as 'cortical inefficiency' (Callicott et al, 2003b).…”
Section: Introductionmentioning
confidence: 85%
“…40,64,88 Heritability: The n-back heritability seems high, at 72.9% for accuracy and 56.4% for reaction time, as found in healthy twins. 89 State independence: Impairment in the n-back task has been reported in patients with schizophrenia at various illness stages, [90][91][92] before and after antipsychotic treatment 92 and independent of illness duration. 91 Cosegregation with illness within family: Cosegregation is suggested by evidence that this impairment is present in relatives of patients with schizophrenia, who perform better than probands.…”
Section: N-back Taskmentioning
confidence: 99%